Early-onset preeclampsia is characterised by an increased vascular tone in internal jugular veins - Dierickx, Inge; Kremer, Cécile; Bruckers, Liesbeth; Gyselaers, Wilfried (Frontiers in Cardiovascular Medicine, 2022)
Purpose: To investigate Doppler characteristics of maternal internal jugular veins in uncomplicated pregnancies versus those affected by hypertensive disorders. Materials and Methods: Venous pulse transit time and venous impedance index were measured at three different locations (right proximal, right distal, left proximal) of internal jugular veins according to a standardised combined Doppler-Electrocardiogram protocol in 5 different groups of pregnant women: uncomplicated pregnancy, early-onset preeclampsia, late-onset preeclampsia, gestational hypertension, and normotensive pregnancies with a small for gestational age foetus. Values of both parameters of the latter four groups were plotted against the reference range of uncomplicated pregnancies at corresponding gestation. Linear mixed models with random intercept were used to investigate gestational changes of venous pulse transit time and venous impedance index at the three internal jugular vein locations within and between the different groups. Results: A total of 83 women were included: 41 with uncomplicated pregnancy, 13 women with early-onset preeclampsia, 25 women with late-onset preeclampsia, 22 women with gestational hypertension and 23 women with normotensive pregnancies with a small for gestational age foetus. Venous pulse transit time values were lower than uncomplicated pregnancy (p ≤0.001) at all three locations in the third trimester of early-onset preeclampsia. Conclusion: Contrary to late-onset preeclampsia and gestational hypertension, early-onset preeclampsia is characterised by a lower venous pulse transit time at internal jugular veins compared to uncomplicated pregnancy, suggesting increased venous vascular tone.